IMPLEMENTASI PERMENDIKBUD NOMOR 15 TAHUN 2018 TENTANG PEMENUHAN BEBAN KERJA GURU, KEPALA SEKOLAH, DAN PENGAWAS SEKOLAH DI SMPN 3 DOPLANG KABUPATEN BLORA - Achmad Dimhari (Master of Public Administration, Universitas Slamet Riyadi, 2022)
The Covid-19 pandemic has changed the implementation of face-to-face (offline)learning to be done with distance learning or online learning. This research is aqualitative research that aims to describe how the implementation of the Ministerof Education and Culture Regulation Number 15 of 2018 at SMPN 3 Doplang. Theresults of the study obtained: Communication indicators have been implementedeffectively, both transformation, clarity, and consistency. Resource indicatorshave not been implemented properly, there is a shortage of civil servant teachers,still need to improve competence, and lack of infrastructure. Dispositionindicators have been implemented well, policy implementers have shown theircommitment in carrying out their duties. Indicators of the bureaucratic structurehave been implemented with.Keywords: Communication, Resources, Disposition, Bureaucratic Structure